The Role of Family Resilience on Family Functioning With Family Communication As Mediator In Generation Z - Zamralita, Zamralita; Wilis, Anastasia Putri Leleng; Angelina, Stephanie (Jurnal Komunikasi, 2024)
The COVID-19 pandemic has profoundly changed the social landscape for younger generations, affecting their communication styles and consequently their mental health. This research investigates the critical role of family resilience in improving family communication and its impact on family functioning, specifically as a strategy to strengthen mental well-being in generation Z. Family resilience is defined as the ability of a family to adapt, recover and thrive amid adversity, which promotes emotional support and shared strength among its members. Family communication includes the exchange of thoughts, feelings and information, which facilitates understanding and connectedness within the family unit. Family functioning refers to how families cope, communicate and interact, involving critical dimensions such as cohesion and flexibility that are important for maintaining healthy relationships. This study used a non-experimental quantitative research design. Data collection used convenience techniques and obtained 251 participants aged 17 to 24 years. The measurement tools used in this study include: Family Assessment Device (FAD) to evaluate family functioning, Walsh Family Resilience Questionnaire (WFRQ) for family resilience, and family communication scale to measure communication dynamics. The results showed a significant positive correlation between family resilience and family functioning (r = 0.90), family resilience and family communication (r = 0.80), and family communication and family functioning (r = 0.83). Family communication was shown to act as a partial mediator in the relationship between family resilience and family functioning. The findings of this study emphasize the importance of building family resilience and family communication to strengthen family functioning, ultimately contributing to improved mental health for generation Z after the COVID-19 pandemic.